2021
DOI: 10.47203/ijch.2021.v33i04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping review of challenges, scope and assessment approaches of teledentistry: an Indian perspective

Abstract: Context: In India, COVID-19 pandemic has limited the utilization and access to dental services owing to the risk of infections transmission. In this context, tele-dentistry could be useful but there is paucity of literature which provides guidance on the scope and challenges for using tele-dentistry in India. Aims: To identify challenges, scope and assessment approaches of tele-dentistry from an Indian perspective. Settings and Design: Scoping Review. Methods and Material: Scoping review was conducted using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A recent study in Nepal revealed that although dentists were familiar with the terminology, they had never practiced it before covid pandemic [56]. Similar observations were available in studies conducted in Saudi Arabia and Iran where 75% dentists were not aware of Teledentistry and in India, 98% of dentists were unfamiliar with teledentistry before the pandemic [57][58][59]. They have struggled with the medicolegal issues concerned with Teledentistry practice especially in rural areas [60,61].…”
Section: Discussionmentioning
confidence: 82%
“…A recent study in Nepal revealed that although dentists were familiar with the terminology, they had never practiced it before covid pandemic [56]. Similar observations were available in studies conducted in Saudi Arabia and Iran where 75% dentists were not aware of Teledentistry and in India, 98% of dentists were unfamiliar with teledentistry before the pandemic [57][58][59]. They have struggled with the medicolegal issues concerned with Teledentistry practice especially in rural areas [60,61].…”
Section: Discussionmentioning
confidence: 82%
“…One review's conclusion about the costs was in contrast with the conclusion stated in the original article and was therefore excluded during the data-selection process [30]. In total, 10 reviews were included in this umbrella review [31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…and was therefore excluded during the data-selection process [30]. In total, 10 reviews were included in this umbrella review [31][32][33][34][35][36][37][38][39][40]. Table 1 presents an overall description of the included reviews characteristics and findings.…”
Section: Resultsmentioning
confidence: 99%
“…The diversity of assessment methods sometimes results in a lack of clarity or comparability [ 20 , 30 , 32 , 35 , 36 , 39 ]; furthermore, this scattered landscape also signals the lack of generalizability and standardization in this field of research [ 32 ]. Moreover, assessment and data collection methods vary widely between the different initiatives (eg, self-reported vs objective measures and qualitative vs quantitative assessment) [ 34 , 37 , 39 , 50 , 98 - 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, eHealth interventions are highly contextual, making it crucial to consider the implementation context and use cases, but the varying contexts and use cases make it quite challenging to find a standardized and generalizable way to assess them [ 15 , 17 , 18 , 100 ].…”
Section: Discussionmentioning
confidence: 99%